The Malay translations of children’s books during the Covid-19 period: an overview - Atikah Zabir (Penerbit Universiti Kebangsaan Malaysia, 2025)
In Malaysia, the pandemic catalysed the publication of Malay-translated children’s digital books focused on COVID-19. However, the pandemic’s influence extended beyond COVID-related themes, affecting overall trends in children’s literature translation. Previous studies illustrate how translation activities in Malaysia have historically reflected societal shifts, from colonial influences to post-independence national identity formation. More recently, a previous study revealed a marked decline in the publication of Malay-translated children’s books during 2020-2021, correlating with the peak of the pandemic. Therefore, this study is carried out to delve deeper into this finding. This study aims to examine the types of texts, source languages, and publishers that defined the Malaysian children’s book translation landscape during this turbulent era. Based on data collected from the National Library’s Online Public Access Catalogue (OPAC), this paper analyses how the pandemic reshaped translation trends in Malay children’s literature and discusses broader implications for the publication industry, with a focus on print publications. The study found that there was a sharp drop in the number of publications during the height of the COVID-19 period. Amid this downward trend, however, Chinese has emerged as the number one source language, surpassing English. Comics and picture storybooks were found to be the most popular types of text, signalling the prevalence of visually engaging and entertaining formats in children’s literature. Finally, the study also found that independent publishers played a pivotal role in sustaining the translation landscape during the pandemic period.